STRATEGI PENGEMBANGAN INDUSTRI KREATIF SEKTOR KERAJINAN BATU KERANG (Studi Hasil Observasi Pada Desa Pulotunda Serang-Banten) - Sukarta Atmaja (LPPM Universitas Banten jaya, 2021)
This study is aimed to find out an alternative strategies of creative industry development of shell rock at pulopanjang. The research uses descriptive research design. The data collected by interview and observation methods which is analyzed by using Internal Factor Analysis (IFE), External Factor Analysis (EFE), and SWOT analysis. The results shows that the internal environment of the industry has a strong position where the strength has a total value of 2.46 compared to the weakness of 0.64. The industry’s position of the outside environment also has strong position where the industry ‘s opportunity has a total value of 1.80 versus threat 1.04. Based on the value of IFE and EFE can be obtained coordinate point in the axis system is 0.91,0.38. The strategy choice is a growth strategy.